Pedagogía y epistemología en el Teeteto de Platón - Prada Marquez, Blanca Ines (Revista Historia de la Educación Colombiana, 2002)
ABSTRACT In the present article a study ofthe Teetetum is offered, putting our attention in the pedagogical and epistemological teachings that underlie inside the debates that sustains Plato with the brilliant mathematic youngster Teeteto: intellectual modesty, amazement, necessary timefor deepening, method (Mayeutic) and the difference between opinión (doxa) and science (episteme). Teachings that are valia today as they were yesterday, for all those who desired to ac^uire fundamental knowledge of any kind, and for the teachers that have taken conscience that the real teacher is not the one that transmits knowledge, but the one that helps his students to be the buüders and craftsmen of their own knowledge.